CHRISTIAN-MUSLIM MORALITY AND FUNDAMENTALISM: The Ethical Perspectives of Karl Barth, and Hasan al-Banna - Izak Yohan Matriks Lattu (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2018)
The article explores Karl Barth and Hasan al-Banna ideas on ethics as the guidance for communal life. Barth emphasizes the command of God as the fundamental theology of Christian values. The prominent German theologian functions as the pivotal scholar in Christian evangelical stream. While al-Banna underlines the centrality of Islamic Sharia to reform Muslim life under colonial circumstances. As it is for Barth in the Christian side, Banna thought influences fundamentalist groups in many Muslim majority countries such as Egypt, Indonesia and many more. Using, a comparative study method, the article concludes that both scholars focus on how scriptures function as the fundamental value for human understanding of social and spiritual life. Although they shared similar issues, Barth, on the one hand, focuses more on how Christianity resist liberalism through the complete acceptance of the holy spirit role in Christian life. Banna, on the other hand, pay more attention to the application of Islamic values as the weapon to fight colonialism